Effect of Low-Energy Ion Implantation on Semiconductors - Elmurotova Dilnoza Baxtiyorovna, Odilova Nilufar Jurayeva, Allayarova Gulmira Xolmuratovna (American Journal of Bioscience and Clinical Integrity, 2026)
This paper provides a physical definition of the concept of ion implantation and a schematic of an ion implantation setup. It is shown that the key parameters for determining ion implantation modes are the energy of accelerated ions and the irradiation dose. The results demonstrate that ions exhibit significant lateral scattering, which leads to changes in the size of the selective implantation regions, where theory allows for the calculation of ion ranges in solids.